Rationale: Photosynthesis of Vascular Plants in Dim Light - Wang, Xiaolin; Wang, Yong; Ling, Aifeng; Guo, Zhen; Asim, Muhammad; Song, Fupeng; Wang, Qing; Sun, Yanguo; Khan, Rayyan; Yan, Huifeng; Shi, Yi (Frontiers in Plant Science, 2020)
The light dominates the earth’s climate and ecosystems via photosynthesis, fine changes of that might cause extensive material and energy alternation. The dim light (typically less than 5 μmol photons m-2 s-1) occurs widely in terrestrial ecosystems, whileand the frequency, duration, and extent of that are increasing because of climate change and urbanization. The dim light is important for the microorganism in the photosynthetic process, but omitted or unconsidered in the vascular high plant, because the photosynthesis in the high-light adapted of the vascular leaves was almost impossible. Here, in this review we propose limitations of photosynthesis in vascular plant leaves, then clarify elucidate the possibility and evidence of photosynthesis in terms of energy demand, stomatal opening, and photosynthetic induction and photosynthesis-related physiological processes in the dim light. This article highlights: the potential and noteworthy influence of the dim light on photosynthesis in vascular plant leaves light, and the research gap of the dim light in model application and carbon accounting.